2000
DOI: 10.1111/j.1945-5100.2000.tb01497.x
|View full text |Cite
|
Sign up to set email alerts
|

New type of radiation of bright Leonid meteors above 130 km

Abstract: Abstract— In this paper, we study the extremely high beginning parts of atmospheric trajectories of seven Leonid meteors recorded by sensitive TV systems equipped with image intensifiers up to apparent magnitude +6.5. For all seven cases, we observed comet‐like diffuse structures with sizes on the order of kilometers that developed quickly during the meteoroids' descent through the atmosphere. For the brightest event with a maximum absolute magnitude of −12.5, we observed an arc similar to a solar protuberance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
4

Year Published

2013
2013
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 7 publications
4
33
0
4
Order By: Relevance
“…The wake is visible from 112.5 km. It closely resembles the behavior of Leonids described in Spurný et al (2000b). The altitude where the ablation starts to be the dominant source of light should be clearly visible in the part of the light curve where the slope of the light curve changes significantly (Koten et al 2006).…”
Section: Atmospheric Trajectory and Orbitsupporting
confidence: 75%
See 2 more Smart Citations
“…The wake is visible from 112.5 km. It closely resembles the behavior of Leonids described in Spurný et al (2000b). The altitude where the ablation starts to be the dominant source of light should be clearly visible in the part of the light curve where the slope of the light curve changes significantly (Koten et al 2006).…”
Section: Atmospheric Trajectory and Orbitsupporting
confidence: 75%
“…The maximum radiometric brightness is then −9.7 at the height of 82.7 km and corresponds to a short flare at 22:29:46.6637 ± 0.0005 s UT (mean time of maximum intensity from nine independent radiometric records) that is not resolved in photographic records. Spurný et al (2000b) divided the appearance of high-altitude meteors into three distinct phases: diffuse, intermediate, and sharp. Diffuse structures, observed above 130 km, are connected with sputtered particles and their subsequent thermalization.…”
Section: Atmospheric Trajectory and Orbitmentioning
confidence: 99%
See 1 more Smart Citation
“…This was quickly confirmed by Spurný et al (2000a), who reported several 1998 Leonid fireballs with beginning heights at 150−200 km. Spurný et al (2000b) analyzed the radiation type of the highest Leonid meteors and suggested that light emitted over 130 km might be due to processes not connected with ablation. All high-altitude meteors from their sample showed comet-like diffuse structures above 130 km, which evolved into typical moving droplets at normal heights.…”
Section: Introductionmentioning
confidence: 99%
“…All high-altitude meteors from their sample showed comet-like diffuse structures above 130 km, which evolved into typical moving droplets at normal heights. Spurný et al (2000b) divided the light curves of high-altitude meteors into three distinct phases: diffuse, intermediate, and sharp. The sharp phase was connected with well-known ablation processes.…”
Section: Introductionmentioning
confidence: 99%